THE IMPLEMENTATION OF THE MALAY ISLAMIC MONARCY PHILOSOPHY IN BRUNEI DARUSSALAM 1984-2019 - Putra, Johan Septian (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
The goal of the article to research about description and substantial the history of the ideology in the state, then investigate the dinamic implementationof the Malay Islamic Monarchy during Sultan Hasanal Bolkiah government. Researcher interested to write this topic because Brunei Darussalam the only one in Southeast Asia the form state is Islamic State with the ideology is Malay Islamic Monarchy. This article uses method of history research, they are: first, heuristic, this step collects the sources. Second, Critical Source, to investigate the authenticity source and examine the information. Third, Synthesis, arrange the facts. Fourth, Writing, explain the result of the research and describe it in descriptive-narative. The result of the research is history civilitation Islamic improve significant since early established the kingdom untill contemporer era. Malay Monarchy Islamic before formed from four consensus, they are: Kanun, Syara’, Adat Istiadat, Resam. Then, the dinamic implementation Malay Monarchy Islamic in five aspect, with part section implemeted in religion aspect, culture aspect and economic aspect, while not implemented in the political aspect and social aspect.